Passive thermal management of an OLED TV display - Nil, Metin; Ozturk, Yavuz; Akgul, Mehmet Bahattin; Catalbas, Mehmet Cem; Nil, Mustafa (Natl Inst Optoelectronics, 2018)
In this study, passive thermal management of a 15 '' OLED TV display is studied. In addition to the OLED display, the effect of other heat generating electronic components on the device is taken into account. Experimental temperature measurements are conducted on the OLED display. The CFD model of the device is developed in order to be able to predict the temperatures and validated with experimental results. A good agreement is obtained between CFD simulation and experimental measurements. To eliminate hot spots and homogenize the temperature distribution, heat spreaders like copper and graphite are used and the effects of them are discussed in detail.
Keywords: OLED; Passive thermal management; CFD; Reliability; Heat spreader